Dietary Supplementation with Inulin Modulates the Gut Microbiota and Improves Insulin Sensitivity in Prediabetes - Xiaojing Wang; Tong Wang; Qian Zhang; Li Xu; Xinhua Xiao (International Journal of Endocrinology)
Aims. Accumulating evidence indicates gut microbiota dysbiosis is involved in metabolic disorders, including prediabetes. The prebiotic inulin has been frequently reported to exert beneficial effects on the host metabolism. Here, we aimed to evaluate whether dietary supplementation with inulin modulates gut microbiota structure in prediabetes, affecting glucose and lipid metabolism. Methods. We performed a prospective single-arm study. A total of 49 subjects with prediabetes (WHO 1999 criteria) were voluntarily enrolled. Each subject received a daily supplement with 15 g of inulin for 6 months. Glucose and lipid metabolic parameters and gut microbiota were analyzed at baseline and at 3 and 6 months after inulin intervention. Intestinal microbiota profile was evaluated using the Illumina MiSeq platform based on V3-V4 bacterial 16S rRNA gene. Results. The mean age of 49 subjects was 56.6 ± 6.9 years and BMI was 25.07 ± 3.02 kg/m2. After 24 weeks of prevention, inulin significantly decreased fasting insulin (2.38 ± 0.50 vs. 2.22 ± 0.62, P=0.03) and 2-hour post-OGTT insulin (4.01 ± 0.77 vs. 3.74 ± 0.76, P=0.02) and improved HOMA-IR (1.05 ± 0.53 vs. 0.85 ± 0.66, P=0.03). Gut microbiota analysis indicated that inulin supplement resulted in an increase in the relative abundance of Actinobacteria, Bifidobacteriales, Bifidobacteriaceae, Lactobacillaceae, Bifidobacterium, Lactobacillus, and Anaerostipes both at 3 and 6 months, while with a decrease in the relative abundance of Alistipes. Spearman correlation analysis revealed altered microbial community was associated with glucose and lipids metabolic parameters. Conclusions. Inulin supplementation improves insulin resistance of prediabetes and exerts beneficial effects on modulating the intestinal microbiota composition. These findings suggest that insulin may be a potentially novel and inexpensive intervention for prediabetes.